Conditional and domain‐specific inactivation of the Tsc2 gene in neural progenitor cells. Issue 4 (13th March 2013) - Fu, Cary; Ess, Kevin C.
<x xml:space="preserve">Abstract</x> Tuberous sclerosis complex (TSC) is a genetic disease characterized by multiorgan benign tumors as well as neurological manifestations. Epilepsy and autism are two of the more prevalent neurological complications and are usually severe. TSC is caused by mutations in either the TSC1 (encodes hamartin) or the TSC2 (encodes tuberin) genes with TSC2 mutations being associated with worse outcomes. Tuberin contains a highly conserved GTPase‐activating protein (GAP) domain that indirectly inhibits mammalian target of rapamycin complex 1 (mTORC1). mTORC1 dysregulation is currently thought to cause much of the pathogenesis in TSC but mTORC1‐independent mechanisms may also contribute. We generated a novel conditional allele of Tsc2 by flanking exons 36 and 37 with loxP sites. Mice homozygous for this knock‐in Tsc2 allele are viable and fertile with normal appearing growth and development. Exposure to Cre recombinase then creates an in‐frame deletion involving critical residues of the GAP domain. Homozygous conditional mutant mice generated using Emx1Cre have increased cortical mTORC1 signaling, severe developmental brain anomalies, seizures, and die within 3 weeks. We found that the normal levels of the mutant Tsc2 mRNA, though GAP‐deficient tuberin protein, appear unstable and rapidly degraded. This novel animal model will allow further study of tuberin function including the requirement of the GAP domain for protein stability. genesis 51:284–292. © 2013 Wiley Periodicals, Inc.